(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: Female abuse and harassment are burning issues of the present times and has shown increasing trend of late.Harassment at workplace is a violation of Human Right.It degrades a person’s privacy and dignity leading to emotional stress,humiliation,anxiety and depression.Hence a study on the prevalence of abuse among female medical students is highly warranted. Methods: A cross sectional study was conducted for a duration of one month among 100 female medical students in Hubli,providing them with pretested semistructured questionnaire after obtaining informed oral consent.The participants were assured of their confidentiality.The data collected,was entered in excel sheet,tabulated and represented as tables and graphs. Conclusion: 95% female students felt that they have been harassed atleast once,among which 53% of the abusers were strangers.Verbal abuse was the most common form of abuse .Majority of them failed to inform higher authorities and had deep psycho social impact.Only a meagre of them were trained in self defense technics.